Pengaruh Pendapatan, Gaya Hidup, Dan Preferensi Risiko Terhadap Perilaku Berhutang Pada Konsumen Muslim : Studi Pada Dealer Honda Nusantara Sakti (NSS) Cabang Pondok Kelapa Bengkulu Tengah - Egi Sustiawan; Romi Adetio Setiawan; Yenti Sumarni (At-Thariqah: Jurnal Ekonomi, 2025)
Each individual has their own responsibility for managing their finances and debts. Debt is one way to overcome a limited budget for something useful. Debt is not always a bad thing. The good or bad of debt depends on the individual themselves as the debt manager. The purpose of this study was to determine and analyze income, lifestyle, and risk preferences that influence debt behavior. This research method is quantitative, data collection using questionnaires to 121 research respondents. The results of the study showed that income influences debt behavior, lifestyle influences debt behavior, risk preferences influence debt behavior, and income, lifestyle, and risk preferences together influence debt behavior. Keywords: Income, lifestyle, risk preferences, debt behavior